ALGORITHMIC SUPPORT OF ASSESSMENT OF THE PREPARED CIVIL AVIATION PILOTS FOR PERFORMING PROFESSIONAL FUNCTIONS - P. M. Polyakov (Naučnyj Vestnik MGTU GA, 2016)
The article deals with the problem of providing an assessment of pilots training for work the airlines in order to ensure flight safety. In this regard, a draft comprehensive methodology for assessing professional training of pilots is offered. It is divided into three stages: 1) introduction into profession; 2) active flight activity and stage in improving professional of skills in case of incidents or accidents in flight.